Parathyroid Carcinoma All-In-One, a Rare Life-Threatening Case With Multiple Systemic Manifestations: Case Report and Review of the Literature - Zelano, Lorenzo; Locantore, Pietro; Rota, Carlo Antonio; Policola, Caterina; Corsello, Andrea; Rossi, Esther Diana; Rufini, Vittoria; Zagaria, Luca; Raffaelli, Marco; Pontecorvi, Alfredo (Frontiers in Endocrinology, 2022)
Parathyroid carcinoma (PC) is an extremely rare disease. Although it may occasionally occur in genetic syndromes, it is more often sporadic. It is usually associated with a consistent secretion of PTH, causing severe hypercalcemia and potentially all clinical conditions due to primary hyperparathyroidism. Management of PC can be challenging: some clinical, biochemical, and radiological features may be useful, but the final diagnosis of malignancy strictly relies on histological criteria. To date, radical surgery is the first-choice treatment and is the only effective therapy to control hypercalcaemia and other clinical manifestations. On the other hand, chemo- or radiotherapy, local treatments or novel drugs should be reserved to selected cases. We report an exceptionally unusual case of life-threatening PC, associated with several systemic manifestations: moderate pancreatitis, portal thrombosis, kidney stones, brown tumours, osteoporosis, hungry bone syndrome (HBS), chondrocalcinosis, neuropathy and depression. The clinical case also represents an opportunity to provide a review of the recent literature, associated to a complete evaluation of the main diagnostic and therapeutic approaches.